Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - Meekan, M. G.; Thompson, F.; Brooks, K.; Matsumoto, R.; Murakumo, K.; Lester, E.; Dove, A.; Hopper, B. (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.